2005
DOI: 10.1309/61xp-4ktl-jywm-5h35
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Significant Kluyvera Infections

Abstract: To determine the clinical significance of Kluyvera isolates at our institution, we retrospectively analyzed clinical microbiology data from January 1999 to September 2003. We identified 11 isolates classified as Kluyvera ascorbata, 7 of which were considered clinically significant pathogens: 3 cases represented urinary tract infections; 2, bacteremia; 1, a soft tissue infection of the finger; and 1, acute appendicitis with a subsequent intra-abdominal abscess. The age distribution of patients was wide, ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 24 publications
1
38
1
Order By: Relevance
“…It has been reported that three (K. ascorbata, K. cryocrescens, K.georgiana) of the four types demonstrated until the present time cause infection in humans and the most common among these is K. ascorbata as in our patient series (8). While K. ascorbata was isolated in 11 of 19 pediatric patients in the literature and K. cryocrescens was isolated in three, typing could not be done in five (3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In Table 1, all pediatric cases in which Kluyvera infection was reported is summarized.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…It has been reported that three (K. ascorbata, K. cryocrescens, K.georgiana) of the four types demonstrated until the present time cause infection in humans and the most common among these is K. ascorbata as in our patient series (8). While K. ascorbata was isolated in 11 of 19 pediatric patients in the literature and K. cryocrescens was isolated in three, typing could not be done in five (3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In Table 1, all pediatric cases in which Kluyvera infection was reported is summarized.…”
Section: Discussionmentioning
confidence: 63%
“…On the 10 th day of treatment, the clinical findings worsened and the body temperature increased again (38,8°C). His laboratory findings were as follows: hemoglogin 9.6 g/dL, leukocytes: 20 500/mm 3 , platelets: 294 000/mm 3 and C-reactive protein: 13.6 mg/dL. Since the findings on the chest x-ray improved, cefepime was discontinued after obtaining blood culture meropenem, vancomycin and amikacin treatments were started considering the hospitalization of the patient.…”
Section: Casementioning
confidence: 99%
See 2 more Smart Citations
“…There are three strains of Kluyvera: Kluyvera ascorbata, K. cryocrescens and Kluyvera species group 3, as reported by Farmer et al [4]. K. ascorbata is the type of species for the genus that was not only been isolated and reported from different cases of human clinical infections: urinary tract infection, sepsis and bacteremia, diarrhea, soft tissue infection, cholecystitis, peritonitis and intra-abdominal abscess, pancreatitis, mediastinitis, urethrorectal fistula [1,3,[11][12][13], but was also isolated from subclinically infected primate Madagascan lemurs [10]. K. ascorbata is an uncommon but clinically very important pathogen.…”
mentioning
confidence: 99%